OPTIMALISASI NILAI PERUSAHAAN MELALUI TAX PLANNING DAN EFISIENSI: ANALISIS MODERASI PERAN GENDER DI DEWAN DIREKSI - Ariyanti, Novie; Rachmawati, Nurul Aisyah (Universitas Kristen Krida Wacana, 2025)
The study's goal was to examine the impact of tax planning and operational efficiency on firm value, with a female board of directors serving as a moderating variable. This study's population consists of 95 enterprises from the IDX's food and beverage industry sector in 2022-2023. This study's data came from the company's annual report, which can be seen on the Indonesia Stock Exchange website. Purposive sampling was used, and 113 firms were selected. The Common Effect Model is the result of selecting panel data models tested in the best research. The results show that tax planning and operational efficiency negatively affect firm value. A female board of director does not impact the relationship between tax planning and operational efficiency on firm value. Keywords: Firm Value, Operational Efficiency, Presence of Female Board of Directors, Tax planning